Epidemiological aspects of syphilis in Itabaiana, Sergipe: an ecological study (Research, Society and Development, 2022)
Objectives: To describe the epidemiological profile of the reported cases and the type of syphilis with the highest incidence in the time frame from 2010 to 2020, in the Municipality of Itabaiana, State of Sergipe, Brazil. Methodology: This is a Descriptive and Observational Ecological Study. Syphilis was addressed in the municipality of Itabaiana-SE in the period from 2010 to 2020. In which the DATASUS was used as sources of information, which evaluates secondary data, not being necessary to submit the work to the Ethics Committee. Analyzing the following variables: Age group, sex, education, social class. Results and discussion: In the present study, it was observed that syphilis in the municipality of Itabaiana in the time frame from 2010 to 2020, 803 cases of syphilis, with the applicability of the variants: gestational age was diagnosed: 145 positive results, in which in the first trimester the result of 51 cases of gestational syphilis was obtained, with 62 reported cases in the second trimester and 31 positive cases of the addressed pathology in the third trimester. Where there was a higher prevalence of cases in the second gestational trimester. Acquired syphilis 490 cases, with a higher prevalence in females with 301. Conclusion: It can be seen through this study the greater prevalence of acquired and gestational syphilis affecting mainly women with low education. The realization of this research contributed to the expansion and development of more severe decision-making in relation to the form of prevention of syphilis, both by the government in the distribution of preventive methods and acceptance of information by the population.